Stop feeling: inhibition of emotional interference following stop-signal trials - Kalanthroff, Eyal; Cohen, Noga; Henik, Avishai (Frontiers in Human Neuroscience, 2013)
Although a great deal of literature has been dedicated to the mutual links between emotion and the selective attention component of executive control, there is very little data regarding the links between emotion and the inhibitory component of executive control. In the current study we employed an emotional stop-signal task in order to examine whether emotion modulates and is modulated by inhibitory control. Results replicated previous findings showing reduced inhibitory control (longer stop-signal reaction time) following negative, compared to neutral pictures. Most importantly, results show decreased emotional interference following stop-signal trials. These results show that the inhibitory control component of executive control can serve to decrease emotional effects. We suggest that inhibitory control and emotion have a two-way connection in which emotion disrupts inhibitory control and activation of inhibitory control disrupts emotion.